In vitro simultaneous mapping of the partial pressure of oxygen, pH and inorganic phosphate using electron paramagnetic resonance. Issue 9 (5th March 2020) - Taguchi, Akihiro; DeVience, Stephen; Driesschaert, Benoit; Khramtsov, Valery V.; Hirata, Hiroshi
Abstract : A simultaneous mapping method was established for the partial pressure of oxygen, pH and inorganic phosphate using electron paramagnetic resonance. Abstract : The partial pressure of oxygen ( p O2 ) and the extracellular pH in the tumour microenvironment are essential parameters for understanding the physiological state of a solid tumour. Also, phosphate-containing metabolites are involved in energy metabolism, and interstitial inorganic phosphate (Pi) is an informative marker for tumour growth. This article describes the simultaneous mapping of p O2, pH and Pi using 750 MHz continuous-wave (CW) electron paramagnetic resonance (EPR) and a multifunctional probe, monophosphonated trityl radical p1 TAM-D. The concept was demonstrated by acquiring three-dimensional (3D) maps of p O2, pH and Pi for multiple solution samples. This was made possible by combining a multifunctional radical probe, fast CW-EPR spectral acquisition, four-dimensional (4D) spectral–spatial image reconstruction, and spectral fitting. The experimental results of mapping p O2, pH and Pi suggest that the concept of simultaneous mapping using EPR is potentially applicable for the multifunctional measurements of a mouse tumour model.